AUM-302, a novel triple PIM/PI3K/mTOR inhibitor, synergizes with RAS inhibition and impedes the growth of pancreatic ductal adenocarcinoma spheroids and organoids - Wen, Emma; Vera, Catalina; Kesavan, Sahaana; Kouassi, Fatim; LaComb, Joseph F.; Zand, Neecki; Tuveson, David A.; Habowski, Amber N.; Baines, Antonio T.; Bialkowska, Agnieszka B. (Frontiers in Pharmacology, 2026)
Pancreatic ductal adenocarcinoma (PDAC) is a significant contributor to cancer-related deaths in the United States. The limited number of well-defined, druggable targets in PDAC has hindered the development of effective treatments. The PIM/PI3K/mTOR pathways, which regulate cell growth, apoptosis, metabolism, and protein synthesis, are often dysregulated in PDAC, leading to various transformed phenotypes, including unchecked cell proliferation. Here, we demonstrate that the triple kinase inhibitor AUM-302 exhibits strong inhibitory efficacy against PDAC growth in 3D formats, including spheroids and organoids. Experiments were conducted using BxPC-3, Capan-2, MIA PaCa-2, and PANC-1 human PDAC cell lines, hF37 2D organoid-derived PDAC cell line, and primary (hF37, hF31, hF44, hT1) and metastatic (hM1a) patient-derived pancreatic cancer organoids. Single- and dual-kinase inhibitors TP-3654, GDC-0941, BEZ-235, respectively, and DMSO were used as controls. The synergy studies were performed using AUM-302 and the RAS inhibitor RMC-6236. Our results showed that AUM-302 significantly inhibited the viability and proliferation of PDAC cell spheroids and organoids more effectively than the controls. The activity of mTOR, AKT, and S6 pathways was decreased as measured by the expression levels of the phosphorylated proteins in hT1 and hM1a organoids after 24 h of AUM-302 treatment, suggesting that AUM-302 reduced the activity of these kinases. Finally, combinatorial assays revealed synergy between AUM-302 and the RAS inhibitor RMC-6236 in reducing the growth of hT1 and hM1A organoids. By blocking kinase activity, AUM-302 demonstrates potent inhibition in PDAC cell lines and organoids across two 3D culture formats. Treatment with this novel triple PIM/PI3K/mTOR inhibitor may also chemosensitize PDAC to other cancer therapies, such as RAS inhibitors.